Implementation and analysis of 5G network identification operations at low signal-to-noise ratio - Ilya Pyatin; Juliy Boiko; Oleksander Eromenko; Igor Parkhomey (Universitas Ahmad Dahlan, 2023)
The article investigates the operations of identifying a cellular network and searching for a cell at various signal-to-noise ratios. The estimation of frequency and time displacement, criteria for detecting the primary synchronization signal are presented. The main contribution of this article is the consideration of the step-by-step execution of the 5G cell search procedure in a complex interference environment. The decoding steps of the primary and secondary synchronization signals are being investigated. This is achieved by analyzing the signals at each step of the correlation algorithm for different signal-to-noise ratios. In order to verify the adequacy of the proposed models, a sequence operation for synchronizing 5G mobile networks with base station signals is considered. The dependence the magnitude of the error vector modulus on the signal-to-noise ratio of a physical broadcasting channel is investigated for three different channel profiles without line of sight. As a result of the experiment, the error vector of the physical broadcast channel changes from 55% to 10%, when the signal-to-noise ratio changes from 0 to 20 dB. In the multiple-input multiple-output (MIMO) mode, we received a 3 dB increase in communication energy efficiency. The findings will be useful for 5G system designers to troubleshoot synchronization problems.